Alocasia spp. Elephant's Ear - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document provides an overview of the Alocasia genus, commonly known as elephant’s ear, highlighting its various species with large, showy leaves1. It details the plant’s characteristics, including its fast growth rate, upright habit, and coarse texture. The document also covers the plant’s adaptability to different soil types and light conditions, its invasive potential, and its uses in landscaping as a border, ground cover, or container plant. Additionally, it discusses the plant’s maintenance needs, pest resistance, and aesthetic contributions to a tropical landscape. Original publication date September 1999.